Shortfall of Domestic Resources to Eradicate Extreme Poverty by 2030. - Fabre, Adrien (Journal of Development Studies, 2025)
In 2015, the Sustainable Development Goals set the eradication of extreme poverty by 2030 as a universally agreed objective. This paper analyses the prospects for achieving this goal country by country. Without a reduction in inequality, even with a very optimistic annual growth rate of 7% between 2022 and 2030, 3% of humans would still be living in extreme poverty in 2030. National capacity to eradicate poverty is then measured using the concepts of antipoverty cap or antipoverty tax required to finance poverty eradication, and income floor (financed by a given income tax). With credible annual growth of 3%, even capping incomes at $7 a day (to finance an increase in incomes for the poorest individuals) cannot eradicate extreme poverty in 5 low-income countries. In other words, neither growth alone nor growth combined with radical domestic redistribution could eradicate extreme poverty by 2030. By contrast, a transfer of just 0.15% of global income could achieve this goal. This could be financed by a 2% tax on individual net wealth above $1 billion.